Development of Interactive Learning Media Articulate Storyline of Indonesian Language Learning in Fourth Grade Elementary School - Nabil Fikri Adam; Petra Kristi Mulyani (STKIP Singkawang, 2023)
The problems at National Elementary School Tugurejo 01 regarding the lack of utilization of technology learning media and learning outcomes that could be more optimal in learning Indonesian. The problem formulation in research examines how to develop, test the feasibility, and test the effectiveness of interactive learning media articulate storyline. The research procedure uses the Borg and Gall model. Development is carried out using the Adobe Illustrator application, which is then converted into an Articulate Storyline. This development research aims to develop learning media and determine the feasibility and effectiveness of interactive learning media based on articulate storylines. The results of the study show that interactive learning is very feasible, with a percentage of eligibility for presentation by media experts of 89% and eligibility for content by material experts of 92%. This media is effective with normality test results. Based on calculations, a sig value of 0.192 was obtained, assuming that the data is usually distributed if the sig value is > 0.05. Based on the results of the n-gain test, the cognitive n-gain score was 0.712, with an average difference of 39.07. So that the n-gain value on cognitive pretest and posttest learning outcomes in large group use trials has a high category, with an effectiveness level of 71,237 Very Effective. The increase in average indicates that interactive learning articulate storylines effectively used as teaching materials and learning media. Suggestions for further research are to apply the media into a more straightforward device so the media can be used in various classroom situations and support character development according to the new curriculum.